PENGARUH LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KEPUASAN KARYAWAN DI RUMAH SAKIT WIDODO NGAWI TAHUN 2018 - Prayitno, Suhadi (Journal Nursing Care and Biomolecular, 2019)
Work environment was one of  efficacy factor in doing a work, but also can result an unsuccess in work execution. ( Kurniasari, 2014). Problems which often happened was work environment and small compensation and also employees satisfaction in doing this work. The aim of this research was analyse influence of work environment and  compensation to employee satisfaction at Widodo Hospital  Ngawi  2018.            This Research type was quantitative with approach of cross sectional.  This Research Sampels are  58  employees at  Widodo Hospital Ngawi. Technique intake of sampel by used  poportional random sampling. Data processed method by used univariat, bivariate, Chi Square and Regresi logistic. Result of this Research was result  from work environment to satisfaction there was significant influence  showing calculation by chi square of work environtment to satisfaction of its result employees with value of sig 0,004, calculation of chi Square compensationi to satisfaction of its result employees 0,003 and calculation of logistic regression work environmental  result of signifikan 0,998 above > 0,05 Ho1 there was not  influence of wor environment  to employees satisfaction. Result bycalculation of result of significan 0,005 under < 0,05 concluding if its result of Ha there was influence of compensation to employees satisfaction. So that its conclusion there was influence of compensation with employees satisfaction.Suggestion which  researcher recommend was expected to hospital to continue improve peaceful and balmy work environment for employees. So that employees can work better, and also improve discipline to employees so can on timed the schedule